What has the new 11th revision of International Classification of Diseases classification brought in the categorization of female sexual dysfunctions? - Pastor, Zlatko; Jonášová, Mirka (Ceska gynekologie, 2022)
In January 2022, the classification of female sexual dysfunctions under the new eleventh revision of International Classification of Diseases came into force. Its definitive integration into practice is expected after a 5-year transition period. The new nomenclature is based on a circular model of female sexual activity, eliminating the Cartesian-dualistic concept of separating individual pathophysiological entities with „non-organic“ and „organic“ etiology. Sexual dysfunctions are evaluated as a complex interaction of psychological, interpersonal, social, cultural, physiological, and by gender-related processes. The new 11th revision of International Classification of Diseases established clear criteria for symptomatology and duration of disorders according to duration, frequency, and exposure to distress. Female sexual dysfunctions may be diagnosed regardless of etiology. The system of qualifiers allows the identification of etiological factors related to health condition; psychological and mental disorders; use of psychoactive substances or medication; lack of knowledge or experience; relational, cultural or gender-related factors. This article summarizes the current situation in the classification of female sexual dysfunctions in a historical context and presents the modus operandi for clinical practice according to current classifications.
Keywords: hypoactive sexual desire disorder; sexuální chování; sexuální dysfunkce psychické; mezinárodní klasifikace nemocí; International Classification of Diseases; Sexual Dysfunction, Physiological; sexuální dysfunkce fyziologická; lidé; Female; vaginismus; orgasmic disorder; sexual arousal disorder; dyspareunia; Sexual Dysfunctions, Psychological; ženské pohlaví; Sexual Behavior; Humans